Information Structure in Maine (SJV) French - Smith, Jane S. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2001)
Lambrecht (1994) proposes the existence of a component of grammar, which he calls information structure, that determines the appropriate lexicogrammatical structure of pragmatically structured propositions. Working within this framework, this paper will explore the status of nominative clitics, left and right detachment, and Pro-drop in the (Acadian) French spoken in Maine’s St. John Valley. Data are taken from a small corpus of speech samples gathered in Madawaska and Fort Kent.